نمو الجراثيم المرجعة للكبريتات في أوساط تحتوي الفوسفوجيبسوم - ناصر أميمة; عليا تميم (Latakia University Journal -Biological Sciences Series, 2019)
إمكانية استعمال مزيج لجماعات الجراثيم المرجعة للكبريتات(Desulfotomaculum, Desulfovibro,(Desulfotomonas معزولة من تربة ملوثة بمشتقات النفط, ومن المياه العادمة الناتجة عن تكرير النفط, واستعملت للتحول الحيوي للفوسفوجيبسوم, وتخفيض الاحتياج الكيميائي للأكسجين COD في المياه العادمة الناتجة عن تكرير النفط. والجماعة الأكثر نشاطاً من الجراثيم المرجعة للكبريتات هي تلك التي عزلت من المياه العادمة الناتجة عن تكرير النفط في وسط البوستجات مع الفوسفوجيبسوم كمصدر للكبريتات, وحسب التحول الحيوي للفوسفوجيبسوم على أساس كبريت الهيدروجين المنطلق في الوسط. كما وجد أن الجراثيم المعزولة فعالة جداً في إرجاع الكبريتات من الفوسفوجيبسوم بنسبة (2.23غ/ل), وتخفيض (90.07%) من الاحتياج الكيميائي للأكسجين في المياه العادمة الناتجة عن تكرير النفط. The possibility of using a mixed community of sulphate-reducing bacteria (SRB) Desulfotomaculum, , Desulfovibro,(Desulfotomonas bacteria were isolated from soil contaminated with crude oil derivatives and petroleum-refining wastewaters and used to biotransformation of Phosphogypsum and reduction of carbon industrial petroleum-refining wastewaters. The most active community of Sulphate-reducing bacteria was isolated from soil contaminated with industrial petroleum-refining wastewaters in culture Postgate with Phosphogypsum as source of sulphates. The biotransformation of Phosphogypsum, calculated on the basis of amount of hydrogen sulphide in cultures. This isolated bacterium was found to be very effective in reduction of (2.23 g/l) sulfate from Phosphogypsum, with (90.07 %) reduction of Chemical Oxygen Demand in industrial petroleum-refining wastewaters.